Cochlear implant aesthetics and its impact on stigma, social interaction and quality of life: a mixed-methods study protocol. Issue 3 (23rd March 2022) - Rapport, Frances; Lo, Chi Yhun; Elks, Beth; Warren, Chris; Clay-Williams, Robyn
Abstract : Introduction: Awareness of the benefits of cochlear implants is low, and barriers such as fear of surgery and ongoing rehabilitation have been noted. Perceived stigma associated with hearing loss also plays a key role, with many adults not wanting to appear old or be identified as a person with a disability. In effect, a cochlear implant makes deafness visible. New technologies have led to a smaller external profile for some types of cochlear implants, but qualitative assessments of benefit have not been explored. This study will examine cochlear implant aesthetics and cosmetics, and its impact on perceived stigma, social interactions, communication and quality of life. A particular focus will be the examination of totally implantable device concepts. A secondary aim is to understand what research techniques are best suited and most appealing for cochlear implant recipients, to assist in future study design and data collection methods. Methods and analysis: This study utilises a mixed-methods design. Three datasets will be collected from each participant with an expected sample size of 10–15 participants to allow for data saturation of themes elicited. Each participant will complete a demographic questionnaire, a quickfire survey (a short concise questionnaire on a topic of research familiarity and preference) and a semi-structured interview. Questionnaire and quickfire survey data will be analysed using descriptive statistics. Interviews will be transcribed and analysed thematically. All participants will be adults with more than 1 year of experience using cochlear implants. Ethics and dissemination: This study has been granted ethical approval from Macquarie University (HREC: 520211056232432) and meets the requirements set out in the National Statement on Ethical Conduct in Human Research. Study findings will be disseminated widely through international peer-reviewed journal articles, public and academic presentations, plain language summaries for participants and an executive summary for the project funder. This work was supported by Cochlear Limited (Cochlear Ltd). The funder will have no role in conducting or reporting on the study.